Legal Reform in the Relocation of Indonesia’s Capital: Challenges and Implications - Jamrudin, Hasrin; Widowaty, Yeni; Satriawan, Iwan; Prasetyoningsih, Nanik; Rettob, Fikram (Journal of Law and Legal Reform, 2025)
Moving Indonesia’s capital city to the archipelago is a strategic policy aimed at addressing development inequality, reducing the burden on Jakarta, and creating a more sustainable center of government. However, the rapid legislative process and lack of public participation raise questions regarding the legitimacy of the policy. This study aims to analyze the legal politics of the National Capital City Law (UU IKN) as well as the social, economic, and environmental implications of relocating the capital city. Using a normative method with a descriptive and comparative approach, this study examines relevant regulations as well as other countries’ experiences in capital city relocation. The results show that capital city relocation faces challenges in governance, protection of indigenous peoples’ rights, as well as environmental impacts such as deforestation and increased carbon emissions. From an economic perspective, while it is expected to boost investment and regional development, the project faces funding constraints as well as social risks for affected communities. Therefore, more inclusive, transparent and sustainability-based policies are needed to ensure the success of this project. Strong regulations, fair compensation mechanisms for affected communities, and strict environmental policies should be top priorities. With a comprehensive approach, the archipelago can develop into a modern, competitive and sustainable capital city.